Implementation Literacy Movement and Pancasila Student Profile in Tegal City - Hubi, Zindan Baynal; Khaedir, Muh; Adi, Panggih Nur; Solehudin, Imam; Sulaiman, Ibnu (Jurnal Civicus, 2025)
This research aims to determine the underlying factors, implementation mechanisms, and implementation impacts related to the implementation of the literacy movement and the Pancasila Student Profile in Tegal City. This research uses descriptive qualitative methods, this allows researchers to enter and interact intensively with sources in the field. Data sources use interviews, observation and documentation. Data analysis uses data triangulation, namely by combining the three data source techniques. The Literacy Movement and Pancasila Student Profile activities were carried out by FKIP Pancasakti University Tegal students who were members of the "FKIP Millennial Summit" activity. The results of this research are that the factors underlying these activities are the existence of juvenile delinquency and the implementation of the Merdeka Curriculum and the Pancasila Student Profile. The activity mechanism begins with communication to the Tegal city bureaucracy and roadshows at several Tegal city educational institutions. Meanwhile, the impact of this activity is that students who are still teenagers through the FGD system realize that juvenile delinquency is an activity that can harm themselves or society, they realize that juvenile delinquency occurs due to a lack of literacy, and they believe that the values of Pancasila are values. which must be implemented in social life.